2012
DOI: 10.1007/s10585-012-9469-1
|View full text |Cite
|
Sign up to set email alerts
|

The histological growth pattern of colorectal cancer liver metastases has prognostic value

Abstract: Little is known about the biological characteristics that determine the prognosis of colorectal cancer (CRC) liver metastases. In previous work we reported three different histological patterns of the tumour-liver interface of CRC liver metastases, termed the pushing, replacement and desmoplastic growth pattern (GP). The purpose of this study was to confirm differences in angiogenic and hypoxic properties of CRC liver metastases with different GPs in a large data set and to study the value of the GP as a progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
101
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 22 publications
7
101
3
Order By: Relevance
“…The present findings conflict with a study conducted by Van den Eynden et al, 3 which evaluated an older cohort of 205 patients hepatectomized for colorectal liver metastases in the period 1995-2005. In this study, no differences in overall survival were found across the growth patterns, yet pushing growth corresponded with poor 2-year survival.…”
Section: Figurecontrasting
confidence: 99%
See 4 more Smart Citations
“…The present findings conflict with a study conducted by Van den Eynden et al, 3 which evaluated an older cohort of 205 patients hepatectomized for colorectal liver metastases in the period 1995-2005. In this study, no differences in overall survival were found across the growth patterns, yet pushing growth corresponded with poor 2-year survival.…”
Section: Figurecontrasting
confidence: 99%
“…In this study, no differences in overall survival were found across the growth patterns, yet pushing growth corresponded with poor 2-year survival. 3 Although survival in all was markedly better in our study, we found a considerably poorer median survival for patients with replacement-type metastases than Van den Eynden et al, 3 in spite of improved medical and surgical management. In addition, the prevalence of the replacement pattern was lower in our population.…”
Section: Figurecontrasting
confidence: 64%
See 3 more Smart Citations